If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 7x = 2x Solving 15 + 7x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 7x + -2x = 2x + -2x Combine like terms: 7x + -2x = 5x 15 + 5x = 2x + -2x Combine like terms: 2x + -2x = 0 15 + 5x = 0 Add '-15' to each side of the equation. 15 + -15 + 5x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 5x = 0 + -15 5x = 0 + -15 Combine like terms: 0 + -15 = -15 5x = -15 Divide each side by '5'. x = -3 Simplifying x = -3
| 12x-6-x=6-5x-5+15x | | 4x+16+14x+26-15x-30=0 | | 6x+9=11x+-36 | | 3x+-3=x+9 | | 3(x+2)=5(x+1)-(2x-1) | | 1/3r-20=-5 | | 3x^5-7x^4+6x^2-14x=0 | | 3(x+2)=5(x+1)-2(x-1) | | 4x-4=-5x-20 | | 40-21(3x+5)-12(3-5x)+8=0 | | 13+4(6x-5)=5(5x+2) | | 4-7=18-x | | x+40=-9 | | 4-7I=18/x | | 25x-16-9x=20+24x-10-10x | | 2t+11-4t=13 | | 12x+15=9x+15 | | 7x-(-8x+12-(24x+12)-2)=9x+62 | | 2(x+4)-12=20 | | 45.99(207.96/100)=4 | | 7x+8x+12-24x-12-2=9x+62 | | 3x-6=4x+4-13 | | 8-3h=2 | | 9x-15y=75 | | =12a(2/3+102/5) | | 39x+12=9x+62 | | 45x-20x= | | 3x-15=-3x-3 | | 2log*9(x)=log*9(8)+log*9(x-2) | | 7x-6+3x-5=8x+5-10x-4 | | 148.75=9.25(-6+t) | | 2log^9(x)=log^98+log^9(x-2) |